UJI EFEKTIVITAS EKSTRAK BUAH PARE (Momordica charantia) PADA MORTALITAS LARVA Aedes aegypti - Prakoso, Gandung; Aulung, Agus; Citrawati, Mila (Jurnal Profesi Medika : Jurnal Kedokteran dan Kesehatan, 2016)
Dengue hemorrhagic fever (DHF) is a major worldwide public health problem. Biolarvicide is a strategy to suppress the incidence of DHF. Bitter melon fruit contains biochemical constituents such as alkaloid, saponin, ﬂavonoid, steroid, and momordicine which have larvicidal eﬀect. This study was aimed to know the eﬀectivity of bitter melon fruit extract as a larvicide of Aedesaegypti larva. The design of this study was experimental. The sample of this study was bitter melon fruit extract. There were 4 concentrationsof bitter melon extract used i.e., 0,8%, 1,6%, 3,2%, 6,4%, and negative control. This study used bioassay method with 20 instar III and IV larvas of Aedesaegypti put into container and were incubated for 24 hours. According to result of Kruskall-Wallis test (p = 0,005) there was a signifcant diﬀerence eﬀectof bitter melon extractonthe mortality of Aedesaegypti larva. The result of Mann-Whitney test showed that there was asignifcant diﬀerence in the eﬀectivity among the concentrationsof bitter melon extract being compared and control solution. The result of probit analysis showed that LC50 and LC90 values were 1,207% and 2,759%, respectively. According to this study, bitter melon fruit extract has larvicide eﬀectonthe mortality of Aedesaegypti.